Coherent $$\mathrm{J}/\psi $$ J / ψ and $${\uppsi '}$$ ψ ′ photoproduction at midrapidity in ultra-peripheral Pb–Pb collisions at $$\sqrt{s_{\mathrm {NN}}}~=~5.02$$ s NN = 5.02 TeV - ALICE Collaboration (European Physical Journal C: Particles and Fields, 2021)
Abstract The coherent photoproduction of $$\mathrm{J}/\psi $$ J / ψ and $${\uppsi '}$$ ψ ′ mesons was measured in ultra-peripheral Pb–Pb collisions at a center-of-mass energy $$\sqrt{s_{\mathrm {NN}}}~=~5.02$$ s NN = 5.02  TeV  with the ALICE detector. Charmonia are detected in the central rapidity region for events where the hadronic interactions are strongly suppressed. The $$\mathrm{J}/\psi $$ J / ψ is reconstructed using the dilepton ( $$l^{+} l^{-}$$ l + l - ) and proton–antiproton decay channels, while for the $${\uppsi '}$$ ψ ′   the dilepton and the $$l^{+} l^{-} \pi ^{+} \pi ^{-}$$ l + l - π + π - decay channels are studied. The analysis is based on an event sample corresponding to an integrated luminosity of about 233 $$\mu {\mathrm{b}}^{-1}$$ μ b - 1 . The results are compared with theoretical models for coherent $$\mathrm{J}/\psi $$ J / ψ and $${\uppsi '}$$ ψ ′ photoproduction. The coherent cross section is found to be in a good agreement with models incorporating moderate nuclear gluon shadowing of about 0.64 at a Bjorken-x of around $$6\times 10^{-4}$$ 6 × 10 - 4 , such as the EPS09 parametrization, however none of the models is able to fully describe the rapidity dependence of the coherent $$\mathrm{J}/\psi $$ J / ψ cross section including ALICE measurements at forward rapidity. The ratio of $${\uppsi '}$$ ψ ′ to $$\mathrm{J}/\psi $$ J / ψ coherent photoproduction cross sections was also measured and found to be consistent with the one for photoproduction off protons.